ANALYSIS OF RAW MATERIAL INVENTORY CONTROL USING THE (EOQ) METHOD TO MINIMIZE THE COSTS INCURRED IN THE PROCUREMENT OF RAW MATERIAL INVENTORY AT PT. X - Mega david (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2024)
This study aims to determine whether the calculation of Economic Order Quantity (EOQ) can be used as Control of Raw Material Inventory at PT. X. This research was conducted by comparing between inventory control methods according to company policy with the Economic Order Quantity (EOQ) method. The research method used is descriptive quantitative, do to collect techniques used are interviews, observation, and documentation. Data analysis techniques used in this study are steps (1) gathering information about the amount of raw material inventory in 2018. (2) processing these data determine the control of raw material inventory based on company policy. (3) analyzing the precessed data using the Economic Order Quantity (EOQ) method. The results of the study prove that Economic Order Quantity (EOQ) is more efficient than the method used by the company. The application of the Economic Order Quantity (EOQ) method can reduce the total costs that must be incurred by the company. Which is IDR 299,399,040. with this (EOQ) method, it can avoid delays in the supply of raw materials, because the supply of raw materials can be ensured constant and according to lead time. Then reaching the research objectives, companies should use the Economic Order Quantity (EOQ) method.